1997
DOI: 10.1037/0096-1523.23.6.1644
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the performance limitations of older and younger adults in a target acquisition task.

Abstract: In a stationary target acquisition task, both 65-year-old and 20-year-old adults exhibited a negatively accelerated curvilinear relationship between the spatial variability of submovement endpoints and average submovement velocity. For high velocities, the variability was greater for the older adults. This elevated motor noise is considered a primary cause of their slower performance. Both age groups also exhibited a linear relationship between submovement duration and the logarithm of submovement relative acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…This assumption is confirmed in a study by Liao et al [30]. They reported that older adults (60-69 years) required a longer duration to achieve the same submovement accuracy as younger adults (18-26 years) in a stationary target-acquisition task (manipulation of a onedimensional isotonic control stick; eight blocks of 8-12 trials each).…”
Section: Motor Learning Of Fine Motor Skillssupporting
confidence: 71%
See 1 more Smart Citation
“…This assumption is confirmed in a study by Liao et al [30]. They reported that older adults (60-69 years) required a longer duration to achieve the same submovement accuracy as younger adults (18-26 years) in a stationary target-acquisition task (manipulation of a onedimensional isotonic control stick; eight blocks of 8-12 trials each).…”
Section: Motor Learning Of Fine Motor Skillssupporting
confidence: 71%
“…A common result of most studies is, as shown for studies focusing on motor functioning (not learning), that there is a general tendency that the performance level is lower for older adults as compared with younger adults [2,7,26,30,39,48,49,55,57,58,64,68,69]. In addition, regardless of learning gains, older adults function on a lower level.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence points towards the necessity of separating different movement stages, such as planning and execution, and provide evidence that these are differentially sensitive to age. Specifically, the movementplanning stage is prolonged, and the start of movements is delayed relative to the go signal [36]. But the actual movement seems affected by age as well, as motion trajectories by elderly people in aiming tasks seem to be less linear and more irregular than in younger subjects [36], and compensatory movements in pursuittracking experiments, at least at high speeds of the target, are slower and more variable [37].…”
Section: General Influence Of Agingmentioning
confidence: 99%
“…Use of this procedure in aging research has revealed that the latencies of the older groups can be predicted accurately from those of young adults by simple mathematical equations [2,7] . Attempts to apply these methods in complex motor tasks have been scarce (see Liao et al [8] for a noticeable exception) and in the lack of metaanalyses, inconsistent estimations exist in the literature. On the one hand, on the basis of reaction-time studies, it has been suggested that sensorimotor functioning could be only slightly affected by aging relative to high-level cognitive processes [2,4,5] .…”
mentioning
confidence: 99%